EAA FlightLink 2G - Skiles, Jeffrey (Proceedings of the Wisconsin Space Conference, 2012)
Founded over half a century ago in Milwaukee, WI, by a pro-active group of aviators interested in building their own aircraft, the Experimental Aircraft Association (EAA) has subsequently expanded its mission to include the history, preservation, display, and ongoing research on antiques, classics, warbirds, aerobatic aircraft, ultralights, helicopters, and contemporary manufactured aircraft. Hundreds of thousands of aircraft and aerospace enthusiasts gather each summer for EAA’s AirVenture Oshkosh, the world’s largest aviation event. Each year, AirVenture re-creates and reinforces its founding atmosphere of challenge, excitement and achievement through educational workshops that promote personal initiative and accomplishment, the gathering of hundreds of exhibitors who share state-of-the-art technology related to the science of flight, and the daily airshow that celebrates the attraction, beauty, and skill of flight past, present and future. Ongoing EAA programs and initiatives available to amateurs and professionals alike include the EAA AirVenture Museum, the Young Eagles, SportAir Workshops, Timeless Voices, the Air Academy, and, since 2005, Women Soar. The Experimental Aircraft Association’s programs serve all demographics from school-age children through adults, with an organizational goal of reaching out to those populations under- represented in aviation, including women and minorities.